Resection Urethroplasty for Urethral Stricture: Preliminary Findings from a Tertiary Care Hospital of Central Nepal - KC, Sudeep Raj; Timilsina, Bhusan Raj; Devkota, Gaurav; Pradhan, Sulav; Lamsal, Sabita; Lamichhane, Nirmal (Journal of College of Medical Sciences-Nepal, 2019)
Background: Urethral stricture is relatively common problem that we encounter in urological practice. As urethral stricture causes progressive narrowing of the urethral lumen, signs and symptoms of urinary obstruction arise. These patients experience obstructive symptoms like poor stream, straining to urinate, incomplete voiding, end dribbling, urinary retention and recurrent urinary tract infections. Methods: A prospective cohort study was carried out in College of Medical Sciences, Chitwan, Nepal. All the patients who were operated with end to end anastomosis for urethral stricture with stricture length not more than 2.5cm from January 2015 to June 2016 was included in this study. These patients were followed up for two year period for recurrence of the stricture and complications. Results: Mean age of patient in this study was 50.55 years, average length of stricture was 1.3 cm. 66.67% (12 patients) had complete success with no recurrence of the stricture. 33.33 % (6 patients) had recurrence of stricture. Out of those 6 patients, 3 had undergone DVIU with no further recurrence of the stricture until the follow up period, one patient was treated with dilatation, two had complete failure and needed re-procedure. Conclusions: End to end anastomosis for short segment stricture had a fairly satisfactory result.